2017
DOI: 10.1016/j.actbio.2017.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to evaluate bacterial contact-killing materials

Abstract: Bacterial adhesion to surfaces of biomaterials implants can be life-threatening. Antimicrobials to treat biomaterial-associated infections often fail due to the bacterial biofilm-mode-of-growth or are ineffective due to antibiotic-resistance of causative organisms. Positively-charged, quaternized surfaces can kill bacteria upon contact and are promising as a non-antibiotic-based treatment of biomaterial-associated infections. Reliable methods to determine efficacies of contact-killing surfaces are lacking, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 41 publications
0
55
0
Order By: Relevance
“…Typically, in "high area to volume tests" a small volume of a microbial suspension is incubated, sandwiched between a thin cover sheet and the test sample, therewith stimulating intimate contact between the microorganisms and the sample 115 . Typical examples are the JIS-Z 2801 116 and "all in one" plating systems (e.g. for yeasts and fungi Petrifilm® Yeast and Mold all-in-one-plating systems, 3M, St. Paul, MN, USA) 117 118 .…”
Section: Methods For Testing Of Materials and Coatings That Resist Fumentioning
confidence: 99%
“…Typically, in "high area to volume tests" a small volume of a microbial suspension is incubated, sandwiched between a thin cover sheet and the test sample, therewith stimulating intimate contact between the microorganisms and the sample 115 . Typical examples are the JIS-Z 2801 116 and "all in one" plating systems (e.g. for yeasts and fungi Petrifilm® Yeast and Mold all-in-one-plating systems, 3M, St. Paul, MN, USA) 117 118 .…”
Section: Methods For Testing Of Materials and Coatings That Resist Fumentioning
confidence: 99%
“…Adhesion-based methods, on the other hand, are suited for evaluating effectiveness of contact-killing surfaces58 ) . In a recent study, van de Lagemaat et al 59 ) found that ‘Petrifilm system’ and ‘Japanese Industrial Standard (JIS Z 2801)’ were the best methods to assess the antimicrobial activity of contact-killing surfaces, if they were used with a complementary assay (zone of inhibition on agar) to exclude bacterial death due to the release of active compound in the medium. Although the JIS Z 2801 has also been adopted as an International Organization for Standardization procedure (ISO 22196:2011), it is a questionable method, in certain respects.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of the efficacy of antimicrobial coatings and materials mostly cultivation-dependent methods have been used, even though depending on the selected cultivation-dependent method, high variations in antimicrobial efficacy can be obtained for the same material ( van de Lagemaat et al, 2017 ). For example, mechanical removal of surface-attached bacteria can potentially lead to release of the antimicrobials, making cultivation-dependent analysis unreliable.…”
Section: Resultsmentioning
confidence: 99%